A clinical analysis of intestinal mucosal necrosis and exfoliation induced by superior mesenteric vein thrombosis: A case report - Lin, Bin; Zhang, Yan-ping; Xue, Lin-ying; Ye, Ying; Tang, Yi; Yang, Chang Shun; Luo, Jie-wei; Gao, Mei-zhu; Fang, Zhu-ting (Frontiers in Surgery, 2023)
Background Superior mesenteric vein (SMV) thrombosis is a rare intestinal ischemic disease. The clinical manifestations of patients differ, and most experience gastrointestinal symptoms. Case summary A 45-year-old female patient presented with persistent abdominal pain and abnormal vaginal bleeding for 7 days. A physical examination revealed significant abdominal tenderness with positive rebound tenderness. A laboratory examination revealed a white blood cell count of 27 × 109/l, hemoglobin level of 52 g/L, and D-dimer of 4.54 mg/l. Enhanced computed tomography revealed a thickening and swelling of the jejunum and ileum in the left upper quadrant and portal vein. Filling defects in the main lumen and branch lumen suggested the possibility of portal vein and superior mesenteric vein thrombosis. Symptoms improved after treatment with low-molecular-weight heparin and warfarin. One month later, the patient developed occasional dull pain in the left lower quadrant, with long strips of discharge. An electronic colonoscopy revealed avascular necrosis and tissue exfoliation of the intestinal mucosa. After the continuation of warfarin therapy, the abdominal pain resolved. Five months later, the patient experienced recurrent abdominal pain and vomiting. A physical examination revealed a blood pressure of 75/49 mm Hg. An incomplete ileus with the portal and superior mesenteric vein thrombosis was diagnosed, partial jejunectomy and gastrointestinal bypass anastomosis were performed, and warfarin was continued postoperatively. Conclusion The intestinal mucosal shedding observed, in this case, was caused by SMV thrombosis, which enriched the clinical manifestations of the disease and provided a new basis for the clinical diagnosis of SMV thrombosis.